Cuidado integral nas dimensões organizativas, técnicas e simbólicas da atenção primária à saúde: narrativas da equipe de saúde e usuários - Silva, Camila Tahis dos Santos (2018)
In the perspective of understanding Primary Health Care (PHC) as a privileged space for meetings that foster dialogue, exposition of subjectivities and the culmination of integral care, as well as locus in which the narratives about the production of care are represented, as the empirical field of this research, which aimed to understand how social subjects (Family Health Team - EqSF and users) conceive integral care in PHC in relation to organizational, technical and symbolic dimensions in a setting in Bahia, Brazil; discuss how comprehensive care is produced by EqSF in APS and examine how EqSF and users attribute meanings and meanings to comprehensive care in PHC. It is a qualitative research conducted with 23 participants divided into two groups: UM group, with 17 respondents from the EqSF, who provide care; group TWO, represented by six (06) users of the selected Family Health Units (USF). The technique of data collection used was the interview and observation. Data analysis was based on the analysis of the narrative, with an approach to Gadamerian hermeneutics. The narratives portray, from the understanding of the symbolic and technical dimension of integral care in PHC, in the face of the subjects' experiences to evidence about the conceptions and / or values related to the health-disease process and its repercussions on the relationships, thus constituting elements for knowledge and discussion of the different visions and forms of understanding obtained with those of multiple glances. The understanding of the symbolic and the technical diverge amidst the ways in which care is narrated and how it happens in the daily life of the Family Health Strategy (ESF). Comprehensive care, even with expanded conceptions in relation to the biomedical model, continues with medicalizing practices. The challenge is no longer in the reorientation of conceptions, but in articulating doing with relationships and subjectivity that permeate practices, seeking the centrality of care in the user, awakening their co-responsibility and self-care, through understanding the health-disease process of more complex form. Finally, care is still centralized in biomedical practices and fragmented in relation to the practice of the various professionals (community health agent - ACS, nurse and doctor), with a focus on family health. In addition, teams need to connect knowledge in different ways to address the needs of users that emerge from their different facets and require shared intervention with appreciation of subjectivity. From the analysis of the narratives and the identification through the observation of the organizational dimension that compose the daily life of the ESF, we perceive the fragility involved in relation to the organization of the PHC within the network of attention, highlighting its selective aspect. Based on this way of organizing services and their relationship with the different levels of care, the analysis provided an understanding of incipient, fragmented and disjointed care in the network.